2012
DOI: 10.5539/apr.v4n2p144
|View full text |Cite
|
Sign up to set email alerts
|

On Particles Mass and the Universons Hypothesis

Abstract: In the logic of the Universons assumption, we deduce the nature of De Broglie wave and periodic mass variation for particles. We verify consistency with quantum mechanics, in particular the Schrödinger equation.We analyze the hypothesis that elementary particle mass is momentum circulating at light speed. We discover resonance rules acting within elementary particles leading to a formula governing the quantization of masses.Applying this formula to the electrons, muons, tauons and quarks, we find resonances th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2012
2012
2014
2014

Publication Types

Select...
6

Relationship

5
1

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 6 publications
0
7
0
Order By: Relevance
“…In two previous papers (Consiglio, 2012a(Consiglio, , 2012b, we showed that the following resonance equation matches all known and estimated masses (i.e. pole masses coming in the SM Lagrangians):…”
Section: Methodsmentioning
confidence: 58%
“…In two previous papers (Consiglio, 2012a(Consiglio, , 2012b, we showed that the following resonance equation matches all known and estimated masses (i.e. pole masses coming in the SM Lagrangians):…”
Section: Methodsmentioning
confidence: 58%
“…Hence the main interest of this paper is in the very existence of the field below, firstly because it could lead to applications that cannot be imagined in the SM theoretical context -but not only. The Feynman-Wheeler absorber theory considers exchanges of energy, and the equation (1) was initially found considering quantized momentum exchanges (Consiglio , 2012), so called Universons (Poher & Marquet, 2012) which is close to the same idea.…”
Section: Discussionmentioning
confidence: 99%
“…All equations in this section are deduced in previous publication (Consiglio, 2012), please refer to it for details and demonstrations; in particular for the mass quantization equation (A3).…”
Section: Formulasmentioning
confidence: 99%
“…-Particles action variation in (A1) leads to de Broglie wave, Schrodinger equation, and uncertainty in their usual form (see Consiglio, 2012). But these three pillars of quantum theories result from classical physics applied to our supposed sub-quantum Universons field.…”
Section: Modelsmentioning
confidence: 99%
See 1 more Smart Citation